PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP MOTIVASI SERTA DAMPAKNYA PADA KINERJA PERAWAT DI RS AMN SUBANG PTPN VIII - Fatihah, Dian Candra; Darmawanti, Nurul (Jurnal E-Bis (Ekonomi-Bisnis), 2018)
This study aimstoobtainempiricalevidenceabout the"Influence of Leadership and Communication Motivation Against Nursesandits Impact on Performance (Studies in Executing Unit Nurse Inpatient Hospital AMN Subang PTPNVIII)". The results ofthis studyare expected to contributeto expanding the horizons for the study ofsciencein general management, hospital management, especially in managing human resources management, especially in terms of the management work of thenursesso that they canbe used asa reference development offuture studies. This researchis expected to improve the performance of nursesin hospitals AMN Subang PTPN VIII in improvingthe performance ofnursesthat will ultimately improvehealth carein hospital AMN Subang PTPN VIII. The method use disdescriptive survey method of verification. Data collectionis to use questionnaires to the nurses who responded, ie all nurses who work in inpatient hospitalunitsAMN Subang PTPN VIII. The data collectionwas conducted inMay 2014. Techniquesof data analysis using path analysis(path analysis). The results showed that leadership, communication and motivationin the category quit ewell although there are still some short coming sand constraintson the factorsthat influence it, as well asthe performance of nursesin health careactivities. Effect of partial (individual) leadership to motivation that is equal to34.3%, the communication of the motivations of 34.4%, the motivationon the performance of 67.1%, whereas the effect together (simultaneously) leadership and communication and their impacton motivationon the performance o fnurses by 68.6% .